The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1982
DOI: 10.1177/00220345820610063401
|View full text |Cite
|
Sign up to set email alerts
|

Cemental Annulation as an Age Criterion in Forensic Dentistry

Abstract: Intact teeth were obtained from three cadavers of known age 56, 67, and 76 years, respectively. Cross-sections 100-150 micrometers thick were taken from the roots using a diamond saw. Individual sections were stained, mounted on glass slides, and photographed on a light microscope. The usual number of years for the eruption of any particular tooth were added to the annulation count to determine the estimated age for that cadaver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
82
0
9

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(100 citation statements)
references
References 14 publications
1
82
0
9
Order By: Relevance
“…Stott et al, first used Tooth Cemental Annulations (TCA), as an age estimation method in humans and concluded that these annulations which were counted from a photograph provided a close estimate of the actual age of the individual from which the tooth was extracted [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stott et al, first used Tooth Cemental Annulations (TCA), as an age estimation method in humans and concluded that these annulations which were counted from a photograph provided a close estimate of the actual age of the individual from which the tooth was extracted [11].…”
Section: Discussionmentioning
confidence: 99%
“…So, this method can be applied to general populations, regardless of systemic or periodontal health [24]. This technique may be extremely valuable in forensic medicine, forensic dentistry, and anthropology [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was further demonstrated in several researches [ 26 -28 ] that resulted in the technique designated as cementochronology or as tooth cementum annulation (TCA). Since its first use in human teeth by Stott et al [ 29 ], it has been widely investigated although with contrasting outcomes. While some considered it to be a promising technique [ 30 -32 ], others advised against it or stated that it had limited potential [ 33 -35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Embora alguns autores tenham alcançado resultados melhores com o uso de cortes desmineralizados e corados Condon et al, 1986;Lipsinic et al, 1986;Solheim, 1995), a relação custo-benefício entre procedimentos para preparo e resultados para lâminas mineralizadas foi vantajosa e escolhida para este estudo, assim como para boa parte dos estudos consultados (Stott et al, 1982;Cipriano, 2001;Jankauskas et al, 2001;Kagerer;Grupe, 2001;Maat et al, 2001;Maat et al, 2006;Wedel, 2007;Aggarwal et al, 2008). Mesmo quando não haja cortadora de precisão disponível, os cortes podem ser feitos com serras "tico-tico" e depois desgastados, de acordo com a técnica modificada de Frost (Maat et al, 2006), embora o manuseio de dentes incluídos, de menor dimensão, possa dificultar o processo.…”
Section: Discussionunclassified